The Implications of Net Profit Margin (NPM) and Return on Equity (ROE) on Share Price at PT. Inti Agri Resources TBK for the Period 2013-2023 - Dewi, Iriana Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2024)
This explore seeks to ascertain and analyze the implications of Net Profit Margin and Return On Equity on Share Prices at PT. Inti Agri Resources Tbk for the period 2013-2023. The findings of the current explore shows that Net Profit Margin partially had zero impact on shares, this is known from the findings of t test where t-count 1.082 < t-Chart 2.30600. Return On Equity partially had zero impact on shares, this is known from the findings of t-test where t-count -0.788 < t-Chart 2.30600. And the findings of the simultaneous test (F test) obtained f-hitung 0.700 < f-tabel 4.46 with a acceptable worthy of of 0.525> 0.05 indicate that Net Profit Margin and Return On Equity concurrently exist no implications on share prices.